Gene Expression in Mammalian Cells and its Applications - Kishwar Hayat Khan (Tabriz University of Medical Sciences, 2013)
The production of proteins in appropriate quantity and quality is an essential requirement of the present time. There appears to be a progressive increase in the application of mammalian cells for proteins production. Expression systems utilizing mammalian cells for recombinant proteins are able to introduce proper protein folding, post-translational modifications, and product assembly, which are important for complete biological activity. This review article is totally based on literature survey. In this article much emphasis has been done on the mammalian expression system. The author focused on different mammalian cell lines that express the gene. The different vector systems that transfer the gene into mammalian cells like plasmid based expression vectors, adenovirus vectors, vaccinia vectors, retroviral vector and baculovirus as vectors were explored. The processes for the transfer of gene into mammalian cells were also reviewed. Application and limitations of mammalian expression system were also focused. The purpose of research in writing this article is to create awareness in researchers, starting their career in gene expression related to mammalian cells. The principal result and major conclusion of this article is to make available the molecular technologies, expression system and applications of gene expression in mammalian cell lines.